Problems of currency exchange - Lawson, Assion G.F. (Technical Centre for Agricultural and Rural Cooperation, 1998)
Assion G.F. Lawson from the Centre d'application agropastoral de Kovié, Lomé, Togo has written to express his frustration relating to the different currencies in which the books featured on pages 14 and 15 of Spore are sold.'We find it very...